Bortezomib for Refractory Immune-Mediated Thrombocytopenia Purpura. (March 2018) - Beckman, Joan D.; Rollins-Raval, Marian A.; Raval, Jay S.; Park, Yara A.; Mazepa, Marshall; Ma, Alice
Abstract : The treatment of refractory immune-mediated thrombocytopenia purpura (ITP) can be challenging. This case report describes treatment of refractory ITP with bortezomib, a proteasome inhibitor. This strategy has been successful in relapsing thrombotic thrombocytopenic purpura but is a novel therapeutic approach for ITP. Further research use of proteasome inhibition in refractory ITP may be warranted.